The Conceptual Apparatus for a Critical Analysis of Speech: Discourse and Authority - Hassane, Hammani (Journal of Humanities & Social Sciences, 2019)
This article sums up the discussion of a deep structural, linguistic and communicative theory. It is related to different but interconnected fields that enable a meticulous approach to the text, for it focuses on different aspects: starting with the outer layer, going through the structure and ending with its reception. It is the critical discourse analysis, which is a modern linguistic approach that works on the explanation and interpretation of language by going beyond the structure of a sentence and the textual interrelations to reach all the dominant social and historical contexts.Its goal is to analyze the discourse from a critical perspective through scrutiny, refutation and questioning. This approach has been part of the discourse analysis theory since the 60s as a body of knowledge that combines different fields, such as politics, sociology, psychoanalysis and rhetoric. It is concerned with studying political communication in society.
Keywords: power; domination; control; social order; social structure; critical analysis of discourse